KALAVA FISHERIES OF PULLUVILA VILLAGE - Mohan, Madan (Indian Journal of Fisheries, 2011)
An account of the Kalava fishery of PuUuvila village, south of Trivandrumin Kerala State, during 1980 and 81 is given in this paper. Species composition ofthe catches, location of the fishing grounds, estimated catches during both the yearsand economics of the fishery are discussed.